Prescrição da modalidade de manutenção de motores elétricos considerando o custo de manutenção e depreciação do ativo - Silva, Cristiano Stefano da (2012)
An efficient management of maintenance activities is normally focused on reliability and availability of equipments, as well as in reducing the costs involved. Aiming to contribute in this sense, the present study proposes a case of study related to the analysis of technical and economic depreciation of electrical motors used in processes of a newsprint industry. In particular, both the Weibull distribution and an economic depreciation analysis were applied to a historic data base containing electric motor failures. The study was carried out for 31 electric motors, which were classified into 10 groups of electric powers. From results obtained for the form factor in 20 years of maintenance and the depreciation analysis was verified that more than 50% of electric motors had premature failures, whereas the rest of equipments had failures of useful life. A statistical analysis of correlation among variables showed that the power of the electric motor had no significance correlation with both the form factor and the number of failure events at 95% of confidence level. However, a significance correlation was found between the power of the electric motor and the maintenance cost involved, as expected. The study showed a practical way of a combined technical and economical analysis applied to electric motors for choosing the better maintenance strategy.